Comparison of the right–left ventricular stroke volume difference evaluated by echocardiography in patients with chronic heart failure complicated with cardiogenic pulmonary edema and pneumonia - Yan, Yaru; Zhao, Haotian; He, Jiapeng; Li, Li; Zhao, Heling; Ye, Yuquan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAlthough B-lines in lung ultrasound may result from diverse etiologies, the presence of left ventricular enlargement and reduced left ventricular ejection fraction (LVEF) generally supports their origin in cardiogenic pulmonary edema (CPE). However, these sonographic findings can also occur in patients with chronic heart failure (CHF) concurrent pneumonia, potentially leading to inappropriate clinical decisions of fluid removal. This study aimed to investigate the diagnostic value of echocardiography-derived right ventricular stroke volume (RVSV) and left ventricular stroke volume (LVSV) difference (ΔSV) in differentiating CPE from pneumonia among CHF patients with acute dyspnea.MethodsThis retrospective observational study enrolled CHF patients presenting with acute dyspnea, subsequently classified as either CPE or pneumonia based on comprehensive diagnostic evaluation. The diagnosis was established by attending physicians through integrated assessment of pulmonary imaging, laboratory biomarkers, and clinical examination findings. Additionally, 30 asymptomatic CHF patients without dyspnea were included as controls. Standard echocardiographic measurements included RVSV, LVSV, tricuspid annular plane systolic excursion (TAPSE) and mitral annular plane systolic excursion (MAPSE), and the ΔSV (difference between RVSV and LVSV) and the ratio of TAPSE to MAPSE (TAPSE/MAPSE) were calculated, respectively. The average value of the ratio between the early diastolic peak velocity of the mitral valve and the diastolic peak velocity of the septal/lateral (E/e′) was considered as the left ventricular filling pressure.ResultsAmong 133 CHF patients with acute dyspnea in the study, 58 had CPE. Between CHF-CPE group and CHF-pneumonia group, the ROC analysis showed that the area under the curve (AUC) of ΔSV was 0.772 (sensitivity 67.24%, specificity 78.67%), and of TAPSE/MAPSE was 0.724 (sensitivity 53.45%, specificity 82.67%). Between CHF-CPE group and CHF-conrtol group, the AUC of ΔSV was 0.830 (sensitivity 87.93%, specificity 76.67%), and of TAPSE/MAPSE was 0.656 (sensitivity 53.45%, specificity 80.00%). Multivariate logistic regression analysis showed that ΔSV was an independent influencing factor, whether between the CHF-CPE group and the CHF-pneumonia group (odds ratio = 1.076, 95% CI: 1.019–1.137), or between the CHF-CPE group and the CHF-conrtol group (odds ratio = 1.066, 95% CI: 1.007–1.129).ConclusionsIn CHF patients with acute dyspnea, the difference between RVSV and LVSV measured by echocardiography is helpful in distinguishing CPE from pneumonia. Nevertheless, further investigation with a larger cohort is necessary to confirm our conclusion.